PERENCANAAN BALAI LATIHAN KERJA TUNA RUNGU DAN WICARA DI KOTA SAMARINDA - Syawaldi, Jefry; Efendi, Arman; Riza, Ahmad (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2020)
Currently, the city of Samarinda has a special disability school with physical hearing and speech ability, it is necessary to place a training hall as a special container. The problem is that the research is planning a working training hall with complementary facilities, where the problem is a creative industry field skills. From the results of the discussion is the analysis site selected on Jl. AWS, District Samarinda Ulu, with a space of 4,509.5 m2, building basic coefficients of 2,254.75 m2 and a green basic coefficient of 5.261 m2. For the analysis of clean water utilities through PDAM water, while the handling of waste water is transmitted through the pipeline to the control body. For the concept of planning Training hall hearing impaired and speech applied organic architecture with material building materials of wood. On the transformation of the form of work training hall namely sunflower shaped divided into major mass, to create a youthful, interesting, unique and cheerful impression to take characteristics of the concept of organic architecture.Â Keywords: physical disabilities, organic architecture, Samarinda.